A new and reusable foundation solution for onshore windmills. (July 2018) - Mohamed, Wael; Austrell, Per-Erik; Dahlblom, Ola
Abstract: A new foundation solution using a cellular raft with an active stabilisation system is proposed in this work. A comparative study of the new foundation and a traditional raft is performed. This study focuses on comparing the load capacity of the mentioned foundation solutions. The results illustrate that a cellular raft with an active stabilisation system gives a substantial enhancement of the load capacity compared to a traditional circular raft. Also, reusing the new foundation solution will provide a significant reduction of the carbon dioxide emissions comparing to the complete dismantling of the existing foundation and building a new one.